2006
DOI: 10.1016/j.febslet.2006.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Unusual histone modifications in Trypanosoma brucei

Abstract: To start to understand the role of chromatin structure in regulating transcription in trypanosomes, we analyzed covalent modifications on the four core histones of Trypanosoma brucei. We found unusually few modifications in the N-terminal tails, which are abundantly modified in other organisms and whose sequences, but not composition, are highly divergent in trypanosomes. In contrast, the C-terminal region of H2A appears to be hyper-acetylated. Surprisingly, the N-terminal alanines of H2A, H2B, and H4, were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 16 publications
1
99
1
1
Order By: Relevance
“…Moreover, their histone sequences and the PTMs that decorate them deviate from what is observed in other eukaryotes (68)(69)(70)(71)(72). For example, histone H3 is relatively free of acetylation, the majority of modifications that have been identified are found on H4, and the C-terminal tail of histone H2A is heavily acetylated in T. brucei (71). Nevertheless, the kinetoplastids clearly use histone acetylation to regulate synthesis of the polycistronic transcripts (73,74).…”
Section: Lysine Acetylation In Protozoan Parasitesmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, their histone sequences and the PTMs that decorate them deviate from what is observed in other eukaryotes (68)(69)(70)(71)(72). For example, histone H3 is relatively free of acetylation, the majority of modifications that have been identified are found on H4, and the C-terminal tail of histone H2A is heavily acetylated in T. brucei (71). Nevertheless, the kinetoplastids clearly use histone acetylation to regulate synthesis of the polycistronic transcripts (73,74).…”
Section: Lysine Acetylation In Protozoan Parasitesmentioning
confidence: 81%
“…Regulation of gene expression appears to be primarily posttranscriptional, via modulation of the splicing machinery that generates the mature mRNAs (67). Moreover, their histone sequences and the PTMs that decorate them deviate from what is observed in other eukaryotes (68)(69)(70)(71)(72). For example, histone H3 is relatively free of acetylation, the majority of modifications that have been identified are found on H4, and the C-terminal tail of histone H2A is heavily acetylated in T. brucei (71).…”
Section: Lysine Acetylation In Protozoan Parasitesmentioning
confidence: 99%
“…1a), and therefore the histone PTMs are likely to be conserved as well. PTMs in T. brucei and T. cruzi histones have mainly been identified by MS analysis (da Cunha et al, 2006;Janzen et al, 2006;Mandava et al, 2007). Mature histones lack the first methionine residue.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of PTMs on the N-terminal tails of histones in Trypanosoma brucei and Trypanosoma cruzi (da Cunha et al, 2006;Janzen et al, 2006;Mandava et al, 2007) has revealed that H4 is heavily acetylated and methylated in its N-terminal tail, and that the H3 tail carries several modifications as well. In contrast to other eukaryotes, the H2A and H2B N-terminal tails have very few modifications, while the H2A C-terminal tail is heavily modified (Janzen et al, 2006;Mandava et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation